Twelve Weeks of Egg Supplementation Does Not Alter Cardiometabolic Parameters in Food Insecure Adults (P08-073-19). (24th October 2019) - Walker, Sam; Hawley, Aubree; Tacinelli, Angela; Baum, Jamie
Abstract: Objectives: To determine if egg consumption for twelve weeks improves markers of cardiometabolic health in adults living in a food insecure environment. Methods: Twenty adults were recruited to participate in a 12-week dietary intervention. Each participant was required to consume two eggs per day, five days per week without altering current dietary habits. Participants were either assigned to a food insecure (FI; n  = 10; 8 female, 2 male; 38.0 ± 5.2 y; 74.2 ± 23.4 kg; BMI 28.5 ± 9.6) or food secure (FS; n  = 10; 9 female, 1 male; 38.4 ± 4.1 y; 79.3 ± 17.1 kg; BMI 28.1 ± 5.4) group. FI was determined using the USDA's six item Short Form Food Security Survey or enrolled in SNAP. Prior to starting the study, participants received nutritional counseling and educational materials regarding food preparation and egg consumption. Data was collected at baseline, 4-, 8-, and 12-weeks. Fasting plasma and serum samples were collected at each visit. Glucose and triglycerides were analyzed using commercially available kits. Height, weight, and waist-to-hip ratio were also measured. Data were analyzed via two-way ANOVA using Prism GraphPad version 8.0. Significance was set at P  < 0.05). Results: There were no significant changes in body weight, BMI, or waist-to-hip ratio in either FI or FS participants. In addition, there was no effect of egg supplementation on plasma triglycerides in either group. Fasting glucose decreased after twelve weeks in the FS group ( P  < 0.05). Conclusions: The results of this study indicate that regular consumption of eggs for twelve weeks does not impact body weight or triglycerides in either FI or FS adults, but may improve blood glucose levels. However, a larger study population and longer intervention period are needed. NCT NCT03412825. Funding Sources: This study was funded by the American Egg Board/Egg Nutrition Center.